Impacts of anthropogenic and natural "extreme events" on global fisheries. Issue 6 (17th August 2018) - Belhabib, Dyhia; Dridi, Raouf; Padilla, Allan; Ang, Melanie; Le Billon, Philippe
Abstract: A broad range of extreme events can affect fisheries catch and hence performance. Using a compiled database of extreme events for all maritime countries in the world between 1950 to 2010, we estimate effects on national fisheries catches, by sector, large‐scale industrial and small scale (artisanal, subsistence and recreational). Contrary to general expectations, fisheries catches respond positively to nearly all forms of extreme events, suggesting a valuable coping or compensation mechanism for coastal communities as they increase their catch after extreme events, but also an opportunistic behaviour by foreign industrial fishing fleets, as industrial catches increase. These effects vary according to country characteristics, with lower coping capacity for coastal communities and higher opportunistic fishing by foreign fleets in countries with poor governance, higher unemployment and direct exposure to prolonged armed conflicts. We also observe an accumulative effect resulting from the aggregation of multiple disasters that deserves further consideration for disaster mitigation. These findings may assist with managing fisheries towards increasing resilience and adaptive capacity such as early detection of potential impacts, protecting livelihoods and food sources, preventing illegal fishing by industrial fleets and informing aid responses towards recovery.